2013
DOI: 10.1002/star.201200170
|View full text |Cite
|
Sign up to set email alerts
|

The effect of xanthan on short and long‐term retrogradation of rice starch

Abstract: The short‐term retrogradation of the rice starch (RS)/xanthan (Xan) mixtures was investigated by Brabender‐E viscograph and dynamic rheometer while the long‐term retrogradation was investigated by DSC and pulsed NMR (PNMR), respectively. RS and 0, 2.5, 5, and 10% Xan (based on RS weight) were prepared into RS/Xan mixtures at the ratios of 100:0, 40:1, 20:1, and 10:1 w/w, respectively. With increasing Xan concentration, the reduced setback (SB) value suggests the decrease of short‐term retrogradation. The gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
80
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 26 publications
21
80
2
Order By: Relevance
“…Krystyjan et al (2015) reported that the PT value of PS was increased by the presence of inulin. The previous studies also found a similar trend in the decrease in SB value with the addition of polysaccharide (Chaisawang & Suphantharika, 2006;Kaur et al, 2015;Tang et al, 2013;Varela et al, 2016). Chaisawang and Suphantharika (2006) found that the PT value of anionic tapioca starch was obviously increased by the addition of xanthan gum and guar gum.…”
Section: Pasting Propertiessupporting
confidence: 63%
See 3 more Smart Citations
“…Krystyjan et al (2015) reported that the PT value of PS was increased by the presence of inulin. The previous studies also found a similar trend in the decrease in SB value with the addition of polysaccharide (Chaisawang & Suphantharika, 2006;Kaur et al, 2015;Tang et al, 2013;Varela et al, 2016). Chaisawang and Suphantharika (2006) found that the PT value of anionic tapioca starch was obviously increased by the addition of xanthan gum and guar gum.…”
Section: Pasting Propertiessupporting
confidence: 63%
“…The increase in PT value is probably due to the synergistic effect between the hydrocolloids and starch granules (Xu et al, 2012). Chen, Tong et al (2014) and Tang et al (2013) found that the presence of xanthan gum or pullulan significantly reduced the SB value of rice starch. Moreover, the increased PT value for PS may be attributed to the strong electrostatic repulsions between the phosphate group of PS and the carboxyl group of AG (Chen, Wang, et al, 2014).…”
Section: Pasting Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Starch-hydrocolloid combinations have been extensively used in food industry [1] with the hope of modifying various characteristics of starch, such as pasting and rheological properties [2,3], retrogradation behaviors [4][5][6], and texture [7]. Taking the pasting properties for example, the addition of hydrocolloids in starch can modify the paste viscosity and overcome the shortcomings of native starch.…”
Section: Introductionmentioning
confidence: 99%